Systemic Glycemic Variation Predicts Mortality of Acute Ischemic Stroke After Mechanical Thrombectomy: A Prospective Study Using Continuous Glucose Monitoring - Deng, Jiangshan; Li, Ling; Cao, Fengya; Wang, Feng; Wang, Hongmei; Shi, Hong; Shen, Li; Zhao, Fei; Zhao, Yuwu (Frontiers in Neurology, 2022)
Objective: We investigated the association of glycemic variation with the clinical outcomes of large vascular occlusion (LVO) induced acute ischemic stroke (AIS) after mechanical thrombectomy (MT). Methods: We recruited consecutive ischemic stroke patients. Glucose levels were assessed through continuous glucose monitoring in 70 patients with AIS who had undergone MT. Metrics including percentages of time of glucose levels above the range (TAR), the hypoglycemic range, and the time within the range (TIR), coefficient of variation (CV), standard deviation (SD), mean of daily differences (MODD), mean amplitude of glycemic excursion (MAGE), largest amplitude of glycemic excursion (LAGE), high blood glucose index (HBGI), and low blood glucose index (LBGI). The outcomes of this observational study were in-hospital mortality, neurological improvement during hospitalization, functional independence, and mortality at follow-up (3 months). The associations of the blood glucose metrics with outcomes were analyzed. Results: The average period of glucose monitoring was 3.5 days, and serum glucose was recorded 728 times after MT for each person. The glycemic variation expressed in standard deviations was independently associated with in-hospital mortality (odds ratio [OR]: 2.8, 95% confidence interval [CI]: 1.276-6.415, p = 0.01) and 3-month mortality (OR: 2.107, 95% CI: 1.013-4.382, p = 0.046) after adjusting for potential confounders. There was no association of glycemic variation with 3-month clinical functional independence. Conclusions: Increased systemic glycemic variation was associated with higher odds of mortality of LVO-AIS after MT.